The effect of site exposure index on the required capacities of aquaculture structures - Dewhurst, Tobias; Rickerich, Samuel; MacNicoll, Michael; Baker, Nathaniel; Moscicki, Zachary (Frontiers in Aquaculture, 2025)
This study investigates the relationship between an ocean site's Exposure Index and the required capacity of finfish, shellfish, and seaweed aquaculture structures. This study provides insights into the efficacy of combining the design significant wave height, peak periods, horizontal wave orbital velocity amplitudes, horizontal current speeds, and water depth into a single index representing exposure. The research builds upon exposure indices proposed previously, and uses Hydro-/Structural Dynamic Finite Element Analysis (HS-DFEA) to quantify the required structural capacities for cultivation structures as a function of exposure index based on representative sites in the German Bight of the North Sea. The selection of 36 sites in this region was based on extreme hydrodynamic and mean bathymetric conditions, utilizing a k-means clustering approach to identify a collection of sites within a broad range of environmental conditions. Through a detailed analysis of the dynamic simulations of each farm type under 50-year storm conditions, we calculated the required capacities of each system for each site. We then evaluated the performance of significant wave height, depth, distance to shore, and the proposed exposure indices as linear predictors of the normalized required capacities. No meaningful linear relationship existed between structural loads and water depth or distance to the nearest coastline. While there is still uncertainty about the utility of exposure indices as a linear predictor of structural loads, this research found that Exposure Velocity was the best linear predictor across structure types by a slim margin, followed closely by the Specific Exposure Energy, Exposure Velocity at a Reference Depth of 5 m, and the Structure-centered Drag-to-Buoyancy Ratio (R2 = 0.69, 0.61, 0.60, 0.60 respectively). This investigation indicates that these exposure indices can be used to communicate what physical ocean conditions mean for an aquaculture structure's required capacity.